2016
DOI: 10.7861/clinmedicine.16-6-565
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the global multidrug-resistant tuberculosis epidemic

Abstract: Multidrug-resistant tuberculosis (MDR TB) IntroductionThe significant threat of the global multidrug-resistant tuberculosis (MDR TB) epidemic has been described as a crisis in the World Health Organization's (WHO's) End TB strategy .1 MDR TB is defined as tuberculosis (TB) caused by Mycobacterium tuberculosis isolates that are resistant to at least both rifampicin and isoniazid.2 The WHO's Global tuberculosis report supplement in 2014 estimated that MDR TB accounts for 3.5% (95% confidence interval (CI) 2.2-4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…To decrease the risk of MDR-TB, it is vital that standardized TRs are implemented by re-treatment TB patients. Some researchers found a highly significant association between the contact with MDR-TB patient and incident MDR-TB [6,14,30]. Our study also suggested that a history of direct contact was one of the strongest independent predictors for incident MDR-TB in individuals with PTBH.…”
Section: Predicting An Individual Patient's Risksupporting
confidence: 72%
See 1 more Smart Citation
“…To decrease the risk of MDR-TB, it is vital that standardized TRs are implemented by re-treatment TB patients. Some researchers found a highly significant association between the contact with MDR-TB patient and incident MDR-TB [6,14,30]. Our study also suggested that a history of direct contact was one of the strongest independent predictors for incident MDR-TB in individuals with PTBH.…”
Section: Predicting An Individual Patient's Risksupporting
confidence: 72%
“…To date, in the research field of MDR-TB control, though some variables, such as sociodemographic, clinical, and microbiological predictors [12][13][14], have been well recognized as determinants of incident MDR-TB risk in TB patients, few studies focused on the status of incident MDR-TB among individuals with PTBH, let alone integrated them so as to comprehensively assess a patient's specific risk of incident MDR-TB. It is now well established from a variety of studies, that the nomogram model is an algorithm with integrating predictors and has been identified as a practical tool of preventive interventions [15].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, more chemotherapeutic agents are still needed. 13 Azole antifungal/antimycobacterial drugs, containing one of the most important classes of heterocycles, such as econazole, miconazole, and clotrimazole, stop the growth of bacteria by inhibiting P450 enzymes (CYP51, CYP121, and CYP130) and show inhibitory potential against MDR-TB in vitro and in vivo (infected mice). [14][15][16] It was also shown that some azole derivatives display a mixed-function oxidase on sterol synthesis in eukaryotic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment regimens have not been able to reduce the number of MDR-TB and XDR-TB infections while achieving reductions in the number of TB infections and death. For this reason, more chemotherapeutic agents are still needed 9 .…”
mentioning
confidence: 99%
“…IR (ATR, cm -1 ); 3232, 3124, 3038, 1603, 1591, 1563, 1517, 1494, 1266 1. H-NMR (DMSO-d6, ppm); δ 10.45 (1H; br; -NH-),9.27 (1H; s; triazole), 8.22 (1H; s; triazole), 7.85 (2H; d; ar. J: 8.8 Hz), 7.84 (1H; s; -N=CH-), 7.78 (2H; d; ar.…”
mentioning
confidence: 99%